Formulation and Evaluation of Vancomycin Loaded Chitosan/Aloe Vera Hydrogel: A Novel Antibacterial Biopolymeric System - Ghandali, Elham Varnaseri; Rastegari, Ali; Mohammadi, Zohreh (Journal of Research Updates in Polymer Science, 2024)
The combination of herbal and biopolymeric agents holds significant potential for enhancing wound healing. Aloe vera, known for its anti-inflammatory, antimicrobial, and regenerative properties, has long been used to treat wounds and burns. Chitosan, as a well-known biopolymer, promotes collagen synthesis, fibroblast recruitment and aiding granulation tissue formation. This study explored the formulation of a chitosan/Aloe vera hydrogel loaded with vancomycin, as a potential wound care product. The hydrogel was prepared using chitosan and aloe vera in 1:1 and 1:2 ratios. After homogenization, 1% vancomycin was incorporated. All physical characterizations, drug loading and drug release studies were performed on prepared formulations. Antimicrobial activity also was evaluated against Staphylococcus aureus and Pseudomonas aeruginosa. Moreover, both physical and performance properties of gels were assessed over three months under room temperature and refrigerated conditions. The study found that the gels remained stable, with no changes in color, flowability, uniformity, or viscosity during stability assessments. Both formulations released their entire drug content within two hours when kept at room temperature and in the refrigerator. No signs of separation or degradation were observed over the three-month period, demonstrating the gel’s stability. Formulations showed acceptable antimicrobial activity against both mentioned bacterial strains. In conclusion, the chitosan/Aloe vera gel containing vancomycin showed desirable properties, making it a promising candidate for wound healing. Its antimicrobial activity and ability to support tissue regeneration suggest it as a valuable treatment for accelerating the wound-healing process.